THE LEVEL OF MOTHER’S KNOWLEDGE ON THE USE OF ZINC IN TODDLERS WITH DIARRHEA IN KARANG PRING HAMLET, RW 01, SUMBER JERUK VILLAGE - Dewi - Rashati (AKADEMI FARMASI JEMBER, 2021)
Diarrhea is influenced by several factors, including environmental conditions, community behavior, community services, nutrition, population, education which includes knowledge, and socio-economic conditions. Diarrhea is defecation in the form of liquid more than three times in one day and lasts for two or more days. The cause of diarrhea is mostly due to infection.Prevention of diarrhea that can be done is to continue breastfeeding, formula milk, and solid baby food, give ORS or sugar-salt solution to replace lost fluids, give foods that contain fiber, and give zinc for 10 consecutive days.The purpose of this study was to determine the level of mother's knowledge of the use of zinc in toddlers with diarrhea in Karang Pring RW 01, Sumber Jeruk village in the realm of knowing, understanding, and application. The method used is descriptive method with cross sectional analysis research design. In this study, the researcher used a validated questionnaire instrument. The sampling technique used total sampling and obtained 44 samples.Based on the results of data analysis, it was obtained that the percentage level of mother's knowledge on the use of zinc in toddlers with diarrhea in Karang Pring RW 01, Sumber Jeruk village for the July 2021 period in the tofu domain was 64.6%, the understanding domain was 74.2%, and in the application domain 72.7 %. The conclusion in this study is that the realm of knowing is categorized as sufficient, the realm of understanding is categorized as sufficient and in the realm of application it is categorized as sufficient. Keywords: Knowledge level, Diarrhea, zinc